Stock Price Analysis of PT Bukit Asam Tbk: A Comprehensive Study - Herlina, Listri; Winar Nugroho, Ilham (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
This study analyzes the stock price condition of PT Bukit Asam Tbk (PTBA) in relation to macroeconomic factors. Using the ordinary least squares regression method, four independent variables from macroeconomics namely Inflation, BI rate, GDP, and Exchange Rate were examined. The results demonstrate that these variables significantly influence PTBA's stock price, with Inflation and GDP positively affecting it, while the BI rate and Exchange Rate have negative impacts. The conclusion emphasizes the importance of understanding external dynamics that affect a company's stock price in complex industries such as coal mining. This research provides strategic insights for investors and corporate management in navigating volatile market challenges.